Book Review: Remodeling GT once again - Alvita K. Nathaniel (Grounded Theory Review: An International Journal)
In their book entitled Rediscovering Grounded Theory, Barry Gibson and Jan Hartman (2014) aim to present grounded theory in a new way with the intention of “forward lookingpreservation” (p. 237). They claim that Rediscovery is an outcome of many conversations in a London pub over the last eight years. The authors tackle both method and methodology as they meticulously describe the context of The Discovery of Grounded Theory (Glaser & Strauss, 1967) and take an authoritative stand on many of the controversies surrounding remodeling of the method in recent years. Rediscovering also includes substantial how-to sections corresponding to chapters in Glaser’s Theoretical Sensitivity (1978). Rediscovery adds explanatory depth in its discussion of the context of grounded theory, but fails to keep many of its promises.